Mechano-Responsive Spiropyran Microbeads: A Facile Fabrication Strategy for Self-Reporting Materials - Jang, Han Gyeol; Jo, Jun Young; Park, Hyung bum; Jung, Yong Chae; Choi, Yong Seok; Sungmin Jung; Lee, Doh C.; Kim, Jae woo (JOHN WILEY & SONS INC, 2023)
Spiropyran (SP) mechanophores are attracting attention as next-generation smart materials that can self-diagnose stress or strain thanks to their capacity for stress visualization with superior sensitivity. However, at present, to achieve the self-reporting functionality, it is considered essential that SP is chemically bonded to a host matrix, which has greatly limited its application. In this paper, mechano-responsive SP beads that can render a material self-reporting by means of simple physical mixing are presented. The synthesis of SP beads is achieved in a microemulsifying needle via dispersion polymerization, and their application to various polymers and aluminum through blending or surface coating methods is reported. The self-reporting property of the specimen, evaluated by in situ measurements of color and full-field fluorescence during deformation, allows both homogeneous and spatially heterogeneous stress distributions to be successfully visualized; the experimental measurements are in good agreement with the finite element simulations. It is also observed that the mechano-response of SP beads is highly dependent on the stiffness of the matrix. The surface-coating method is demonstrated to possess great advantages in terms of applicability, sensitivity, and scalability, facilitating accurate self-diagnosis of the onset and propagation of damage in real time, even under complex stress conditions.